2006
DOI: 10.1111/j.1471-4159.2006.04132.x
|View full text |Cite
|
Sign up to set email alerts
|

Uracil nucleotides stimulate human neural precursor cell proliferation and dopaminergic differentiation: involvement of MEK/ERK signalling

Abstract: Isolation and propagation of neural stem cells derived from human brain tissue uniquely enables the study of human neurogenesis in vitro. In addition, ex vivo-expanded human neural stem/precursor cells (NPCs) may offer novel therapeutic strategies. We investigated the effects of extracellular nucleotides on the proliferation and differentiation of human mesencephalic neural stem/precursor cells (hmNPCs). When combined with the mitogens epidermal growth factor and fibroblast growth factor 2, UTP (1 lM) boosted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 39 publications
4
59
1
Order By: Relevance
“…In line with the previous reports, UTP and PSB1114 (P2Y 2 R-specific agonists) induced robust phosphorylation of ERK1 and ERK2 in a time-dependent manner. Our results suggest that MAP kinase signaling is activated by Ca 21 and PKC, and it appears that nucleotide-mediated P2YR activation initiates similar signaling cascades with similar cellular consequences in muscle and neurons (Tu et al, 2000;Choi et al, 2003;Milosevic et al, 2006;Siow et al, 2010). In our results, the responses of UTP in Ca 21 mobilization and Erk phosphorylation in Fig.…”
Section: Discussionsupporting
confidence: 66%
“…In line with the previous reports, UTP and PSB1114 (P2Y 2 R-specific agonists) induced robust phosphorylation of ERK1 and ERK2 in a time-dependent manner. Our results suggest that MAP kinase signaling is activated by Ca 21 and PKC, and it appears that nucleotide-mediated P2YR activation initiates similar signaling cascades with similar cellular consequences in muscle and neurons (Tu et al, 2000;Choi et al, 2003;Milosevic et al, 2006;Siow et al, 2010). In our results, the responses of UTP in Ca 21 mobilization and Erk phosphorylation in Fig.…”
Section: Discussionsupporting
confidence: 66%
“…There are few studies in the literature that show that P2Y6 receptor activation is involved in differentiation processes such as osteogenic, monocytic, or dopaminergic differentiation. 17,[33][34][35] Moreover, it has been previously reported that P2RY13 activation by ADP induces autophagy in hepatoma cell lines. 36 However to the best of our knowledge, this is the first description of purinergic receptor-mediated differentiation being dependent on autophagy induction.…”
Section: Discussionmentioning
confidence: 97%
“…These data suggest the involvement of purinergic signaling in dopaminergic cell differentiation and possible applications for purinergic receptors in in vitro differenti-ation cultures for posterior PD cell therapy [74]. However, more studies are needed to clarify whether extracellular nucleotides may contribute to favorable endogenous niches for stem cell transplantation or even recruit endogenous NPCs for dopaminergic differentiation.…”
Section: Parkinson's Diseasementioning
confidence: 94%
“…Exogenous molecules are known to guide neural differentiation and are responsible for the high grade of phenotype specification, including induction of axonal growth and establishment of synaptic contact [73]. Milosevic et al [74] detected P2Y4, P2Y6, and P2X4 receptor expression in cultured human NPCs from human fetal midbrain. UTP and UDP are known as agonists of the P2Y2/P2Y4 and P2Y6 receptors, respectively [75].…”
Section: Parkinson's Diseasementioning
confidence: 99%